The Relationship Of Knowledge With The Incident Of Typhod Fever On Children At Dr.Fauziah Hospital Bireuen District In 2024 - Sitti Muthmainnah; Novianti, Novianti; Asmaul husna; Putry Hendriyani (Sean Institute, 2024)
Data from the Indonesian Health Profile in 2022 shows that 41,081 cases of typhoid and paratyphoid fever sufferers were hospitalized in hospitals with a death rate of 279 cases (Ministry of Health, 2022). Several factors play a role in the incidence of typhoid fever, including: environmental factors, knowledge, attitudes and actions. According to the Ministry of Health in 2022, feces disposal, clean water facilities, food sanitation, personal hygiene, the habit of snacking or eating outside the home, as well as a history of typhoid fever in the family is a factor that is thought to be involved in the incidence of typhoid fever. The population in this study were all children aged 5 to 14 years who were diagnosed with typhoid fever and treated in the pediatric ward from January to June 2024, totaling 67 cases. A sample is a part of a population that has certain characteristics or conditions to be studied. The sampling technique used in this research was Total Sampling, namely the entire population was used as a sample, namely 67 cases. This research is analytical with a cross sectional design with data processing methods using Editing, Coding, Tabulating and Entry. The results of the chi-square statistical test between knowledge and the incidence of Typhoid Fever in children obtained a p value (0.002) < α (0.05), meaning that H0 was rejected, and Ha, accepted, so it can be concluded that there is a relationship between knowledge and the incidence of Typhoid Fever. at Dr. Hospital. Fauziah. It is hoped that Dr. Fauziah Bireuen Regency As a measure to prevent typhoid fever in children, Dr. Hospital. Fauziah Bireuen Regency was advised to improve health education programs for parents about the importance of sanitation, food hygiene and vaccination.